PEMANFAATAN ARSIP LABORATORIUM DAN REKAM MEDIS DALAM ANALISIS PROFIL INFEKSI CANDIDA ALBICANS PADA URINE WANITA PENDERITA DIABETES MELITUS DI PUSKESMAS MUJUR PRAYA TIMUR TAHUN 2023 - Muhammad Aditya Rachman; Erni Erdita (Nusadaya Journal of Multidiciplinary Studies, 2026)
Laboratory and medical record archives represent important forms of dynamic records in healthcare institutions that support clinical evaluation and scientific accountability. This study aims to analyze the profile of Candida albicans infection in urine of women with diabetes mellitus based on laboratory and medical record archives at Mujur Public Health Center, East Praya, in 2023. The research employed a descriptive method with a retrospective approach through archival document analysis. The data were obtained from laboratory examination records and patient medical records. The results showed that Candida albicans infection was found in several urine samples, particularly among patients with high blood glucose levels and longer duration of diabetes. From an archival perspective, properly managed records enable systematic, accurate, and traceable data analysis. However, inconsistencies in documentation may affect data quality. This study highlights the importance of strengthening archival management systems to support reliable healthcare data and improve service quality.